A Deadly Wind : The 1962 Columbus Day Storm - Dodge, John (Columnist) (Book collections on Project MUSE., 2018)
The Columbus Day Storm of 1962 was a freak of nature, a weather outlier with deadly winds topping one hundred miles per hour. The storm killed dozens, injured hundreds, damaged more than fifty thousand homes, and leveled enough timber to build one million homes. To find an equally ferocious storm of its kind, fast-forward fifty years and cross the continent to Superstorm Sandy's 2012 attack on the East Coast. While Superstorm Sandy was predicted days in advance, the Columbus Day Storm caught ill-equipped weather forecasters by surprise. This unrivalled West Coast windstorm fueled the Asian log export market, helped give birth to the Oregon wine industry, and influenced the 1962 World Series. It remains a cautionary tale and the Pacific Northwest benchmark for severe windstorms in this era of climate change and weather uncertainty. From its genesis in the Marshall Islands to its final hours on Vancouver Island, British Columbia, the storm plowed an unparalleled path of destruction. In A Deadly Wind, veteran journalist John Dodge tells a compelling story spiced with human drama, Cold War tension, and Pacific Northwest history. This is a must-read for the tens of thousands of storm survivors, for history buffs, and for anyone interested in the intersection of severe weather events and climate change.